Hypanthropos: On Apprehending and Approaching That Which is in Excess of Monstrosity, with Special Consideration given to the Photography of Edward Burtynsky - Witmore, Christopher (Journal of Contemporary Archaeology, 2019)
Offering a more precise epithet for that which has emerged under the provisional label of the “Anthropocene”, this article trains its lens on some of the more-than-monstrous things that have revealed themselves in our calamitous times. It raises questions about how archaeologists are to apprehend and approach objects that differ in scale, speed, makeup, and efficacy from anything our field has ever dealt with. But rather than honing its analytical edge exclusively with the latest science, it also ventures in another direction to explore some of the powers of art by considering the work of the Canadian photographer Edward Burtynksy. Finally, it makes a few closing remarks on the role of our profession in this new archaeological era.